2008
DOI: 10.1021/la800925t
|View full text |Cite
|
Sign up to set email alerts
|

PtRu Nanoparticles Supported on 1-Aminopyrene-Functionalized Multiwalled Carbon Nanotubes and Their Electrocatalytic Activity for Methanol Oxidation

Abstract: A new synthesis method for the preparation of high-performance PtRu electrocatalysts on multiwalled carbon nanotubes (MWCNTs) is reported. In this method, bimetallic PtRu electrocatalysts are deposited onto 1-aminopyrene (1-AP)-functionalized MWCNTs by a microwave-assisted polyol process. The noncovalent functionalization of MWCNTs by 1-AP is simple and can be carried out at room temperature without the use of expensive chemicals or corrosive acids, thus preserving the integrity and the electronic structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
173
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 44 publications
7
173
0
6
Order By: Relevance
“…It was demonstrated before that PDDAMWCNTs could serve as a very useful support for synthesis of platinum and also palladium sheets [32]. Also, bimetallic PtRu nanoparticles were synthesized using similar method but instead PDDA 1-aminopyrene was used [17]. In the present work, we adapted the approach mentioned above to fabricate the PtRu alloyed nanoparticles on PDDA functionalized MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated before that PDDAMWCNTs could serve as a very useful support for synthesis of platinum and also palladium sheets [32]. Also, bimetallic PtRu nanoparticles were synthesized using similar method but instead PDDA 1-aminopyrene was used [17]. In the present work, we adapted the approach mentioned above to fabricate the PtRu alloyed nanoparticles on PDDA functionalized MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies clearly show that application of carbon nanotubes as carriers may result even in higher electrocatalytic activities in comparison to conventional carbon nanoparticles. But, to achieve this goal, graphene surfaces of carbon nanotubes need to be chemically modified or functionalized [17]. Properly functionalized MWCNTs not only assure physical separation and large dispersion of reactive sites at the catalytic interface but they also act as rigid templates for well-shaped and uniformly sized noble metal nanoparticles [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs have unique properties, such as large surface area, high thermal stability, excellent electrical conductivity and well-defined structure with inner hollow cavities and high aspect ratio, which make them extremely attractive in many potential fields, such as energy storage, electronics and catalysis. [2][3][4] After their decoration with suitable transition metals (Pt, Pd, Ru, Ag, Ni, Au, et al ), CNTs have been found to be active as heterogeneous catalysts in hydrocarbon processing [5][6][7] and electrode reactions of fuel cells, 8 to show a high hydrogen storage capacity, 9 and to be very sensitive in optical and electronic applications as chemical sensors. 4 An understanding of the cooperative interaction between CNTs and the loaded metal particles may provide means to enhance their performance in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…The I D /I G ratio of Fe-CEW is 1.07, closed to the value of XC-72 but smaller than that of CEW (1.14), indicating that (i) the Fe-CEW exhibits less defects sites than the CEW, which may be caused from the original defect sites that is covered by the doped Fe atoms, as reported in literature for the 1-aminopyrene-functionalized multi-walled carbon nanotubes; 25 (ii) the Fe-CEW possesses much better electric conductivity compared to CEW, which means a higher current density and excellent performance for ORR. 26 Fig. S4, ESI3 displays TGA and DTG profiles of the decomposition process of EW and Fe doped egg white (Fe-EW), from which we can obtain information on residual masses at different temperatures.…”
mentioning
confidence: 99%